2020
DOI: 10.1001/jamanetworkopen.2020.29121
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Work Life Quality of Nursing Home Care Aides in Canada

Abstract: This cross-sectional study describes care aides’ characteristics and quality of work life in Western Canadian nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 4 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Those occupying the lower end of the occupational hierarchy, moreover, described experiencing distress and burnout in relation to insufficient time to practice good treatment. These health problems have been identifed in other research on care aides (Song et al, 2020;Tremblay, 2017) and demonstrate that the provision of sustainable good treatment in residential care settings is dependent on what Casagrande (2016) describes as 'double good treatment:' good treatment of both older adults and care staff.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Those occupying the lower end of the occupational hierarchy, moreover, described experiencing distress and burnout in relation to insufficient time to practice good treatment. These health problems have been identifed in other research on care aides (Song et al, 2020;Tremblay, 2017) and demonstrate that the provision of sustainable good treatment in residential care settings is dependent on what Casagrande (2016) describes as 'double good treatment:' good treatment of both older adults and care staff.…”
Section: Discussionmentioning
confidence: 90%
“…8.The term ‘care aide’ is used as the English translation of ‘préposé.es aux bénéficiaires’ because it is one of the more common terms used to describe the work of assisting residents in activities of daily living (ADL), ensuring their safety and comfort, and maintaining their hygiene (see Estabrooks, et al, 2020; Song et al, 2020). …”
mentioning
confidence: 99%
“…On one hand stand residents’ and relatives’ acute care needs and, on the other hand, care providers missing out on tasks fulfilling these needs. Missed care has been associated not only with high workload and inadequate teamwork but also with care workers’ perception of inadequate staffing ( Nelson & Flynn, 2015 ; Song et al, 2020 ; Zúñiga et al, 2015a ). Indeed, findings of studies in the United States ( Nelson & Flynn, 2015 ) and Canada ( Song et al, 2020 ) indicate that tasks our participants considered acute such as taking residents for walks, talking to them, toileting, bathing, feeding, and dressing them, are reported by up to 57.4% of registered nurses as missed during their last shift worked, with up to 65.4% reporting rushing at least one such task ( Nelson & Flynn, 2015 ; Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Missed care has been associated not only with high workload and inadequate teamwork but also with care workers’ perception of inadequate staffing ( Nelson & Flynn, 2015 ; Song et al, 2020 ; Zúñiga et al, 2015a ). Indeed, findings of studies in the United States ( Nelson & Flynn, 2015 ) and Canada ( Song et al, 2020 ) indicate that tasks our participants considered acute such as taking residents for walks, talking to them, toileting, bathing, feeding, and dressing them, are reported by up to 57.4% of registered nurses as missed during their last shift worked, with up to 65.4% reporting rushing at least one such task ( Nelson & Flynn, 2015 ; Song et al, 2020 ). In contrast to the above-cited studies, Zúñiga and colleagues (2015a , 2015b ) found that up to 76% of Swiss NH care workers rarely or never miss care related to activities of daily living; however, if necessary, care workers sacrifice attention to residents’ and their families’ social needs ( Zúñiga et al, 2015a , 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…As many as 90% of people with dementia will experience BPSD, which are associated with distress among residents and caregivers 25 . In Canadian care homes, up to 43% of care aides experience daily aggression such as biting, hitting, or pushing from residents or their relatives 26,27 . Care aides provide up to 90% of direct care and essential social support for residents 28,29 .…”
Section: Introductionmentioning
confidence: 99%